Groundwater phosphorus contamination caused by cultural activities (case study: Babol City) - Hamedi, Hamideh; Ehteshami, Majid; Dolati, Siyavash; Rasouli, Seyed Abbas (International Journal of Engineering and Technology, 2015)
Background: By economic development of societies and population growth there is an immense need for more food resources. Therefore, artificial fertilizers are a necessity to enhance agricultural productions. Fertilizers could leach into groundwater by man’s cultural activities and contaminate soil and groundwater.Objectives: The main objective in this research is to evaluate the ability of LEACHN model to simulate the phosphorus movement in soil medium causing groundwater contamination.Methods: LEACHN model was used to simulate. The required data to operation of the model are given from the Haraz Extension and Technology Development Center in Mazandaran, Iran.Results: The model was tested in order to verify its prediction value; with a correlation coefficient of 92.3% accuracy. The mean bias error of modeling was equal to -0.087. A sensitivity analysis indicated that the phosphorus concentration in the soil was slightly sensitive to soil saturated hydraulic conductivity changes, but was highly sensitive to changes in soil bulk density.Conclusions: The results showed that the model can accurately simulate phosphorus concentration in soil profile. The result of scenario modeling showed that the amount of phosphorus leakage was directly proportional to precipitation changes and soil permeability.